2020
DOI: 10.1016/j.jcv.2020.104659
|View full text |Cite
|
Sign up to set email alerts
|

Panbio antigen rapid test is reliable to diagnose SARS-CoV-2 infection in the first 7 days after the onset of symptoms

Abstract: Highlights The new antigen tests for COVID19 are an indispensable tool in the control of the pandemic due to their adequate sensitivity and specificity. The implementation of the point of care technique in primary care is feasible and has good results. Less than 5 days of evolution of the onset of symptoms and CT less than 27 in the PCR would define the results of the antigen techniques.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
186
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(227 citation statements)
references
References 11 publications
33
186
5
3
Order By: Relevance
“…In line with our results, previous studies analyzing the performance of different antigen tests reported a consistently high specificity but a broad spectrum of sensitivity that seems to be lower than the sensitivity range reported by the manufacturers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. These differences might be due to multiple factors, such as the moment of testing in the infection phase, the cohort size, the sampling site, the specimen quality, and the handling and preparation, or related to the distribution of CT-values using non-standardized rRT-PCR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our results, previous studies analyzing the performance of different antigen tests reported a consistently high specificity but a broad spectrum of sensitivity that seems to be lower than the sensitivity range reported by the manufacturers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. These differences might be due to multiple factors, such as the moment of testing in the infection phase, the cohort size, the sampling site, the specimen quality, and the handling and preparation, or related to the distribution of CT-values using non-standardized rRT-PCR.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous commercial assays are now available [ 5 ], but there are limited data on their clinical performance. Based on previous studies, the sensitivity of SARS-CoV-2 Ag-RDTs range between 22.9% and 93.9% when compared to rRT-PCR [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Apart from sensitivity, it is important that such tests identify potentially contagious individuals to reduce SARS-CoV-2 transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, we identified at least four studies that evaluated the Panbio COVID-19 Ag rapid test [ 8 , 12 , 14 , 17 , 22 ]. In a population of 341 patients, Fenollar et al found a specificity of 94.9% and a good sensitivity but only for samples with Ct values <25 (i.e., 94.2 to 100%) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Head-to-head comparisons of AD test performance for SARS-CoV-2 detection are scarce. The majority of the studies only included few patients, precluding a wide characterization of the “real-life” performance of these devices [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Recently, a Cochrane study found an average sensitivity of only 56.2% (95% confidence interval (CI): 29.5–79.8%) for rapid AD (RAD) tests [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two recently evaluated RAD assays (BD Veritor System and the Panbio™ COVID-19 Ag Rapid Test Device) may be used as a proxy for SARS-CoV-2 cultured from respiratory tract specimens, thus allowing reasonably accurate prediction of contagiousness [ 2 , 3 ]; yet this assumption awaits further validation in larger cohorts. The possibility of using RAD tests to identify SARS-CoV-2-infected asymptomatic contacts of COVID-19 patients is appealing, as it could effectively contribute to minimize community SARS-CoV-2 spread through early detection of highly infectious individuals [ 1 ], yet little is known about how RAD tests perform in this population group [ [4] , [5] , [6] ]. Here, we report on the performance of the Panbio™ COVID-19 Ag Rapid Test Device (Abbott Diagnostic GmbH, Jena, Germany) conducted at POC in this setting.…”
Section: Introductionmentioning
confidence: 99%